2008
DOI: 10.4140/tcp.n.2008.223
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Services Provided by Pharmacists: Is the Public Willing to Pay for Them?

Abstract: Respondent's willingness to pay for pharmacist cognitive services appeared to be correlated with insurance coverage and out-of-pocket expense and inversely proportional to the amount of out-of-pocket expense to the patient. Of those willing to use pharmacist cognitive services, 47% of the sample were willing to pay 100% out-of-pocket for pharmacist cognitive services, 70% were willing to pay a copay of 20%, and 85% were willing to use these services if insurance paid 100% of the cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…A cross-sectional study of patients, 18 years of age and older, found that 70% of their sample population had a WTP of 20% of the total OOP cost for a pharmacist's cognitive (MTM and educational) services. 6 The respondents' WTP amount was correlated with insurance coverage and OOP expense. Findings in our Medicare population are dissimilar to these findings where younger respondents' WTP for cognitive services increased as OOP payments decreased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional study of patients, 18 years of age and older, found that 70% of their sample population had a WTP of 20% of the total OOP cost for a pharmacist's cognitive (MTM and educational) services. 6 The respondents' WTP amount was correlated with insurance coverage and OOP expense. Findings in our Medicare population are dissimilar to these findings where younger respondents' WTP for cognitive services increased as OOP payments decreased.…”
Section: Resultsmentioning
confidence: 99%
“…results from prior WTP studies may differ from our study in that their patient populations included more diverse populations (e.g., younger patients), whereas our study solely focused on Medicare beneficiaries. 6 Furthermore, our population was asked their WTP after receiving the MTM concurrently with Medicare Part D enrollment/re-enrollment assistance. As such, their perceived economic value of services reflects their perception of the delivered services.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, they focused on four aspects: evaluating patients' awareness or understanding of the service, exploring patients' experiences or expectations of the service, investigating patients' perceived barriers of using the service, and assessing patients' attitudes towards expanded pharmacist roles of providing healthcare services other than traditional dispensing. For another small portion of the literature, although studies were conducted in the context of pharmaceutical care, researchers were more interested in measuring patients' willingness-to-pay (WTP) for the service (Friedrich, Zgarrick, Masood, & Montuoro, 2010;Hill & Dowse, 2007;Hong, Liu, Wang, Brown, & White-Means, 2011;Schuh & Droege, 2008;Tootelian, Rolston, & Negrete, 2005;Waszyk-Nowaczyk et al, 2014;Woelfel et al, 2014). One study focused on comparing pharmacy patrons' satisfaction between urban population and suburban population (Malewski, Ream, & Gaither, 2015).…”
Section: Patient Perception On Pharmaceutical Care Servicesmentioning
confidence: 99%
“…A small portion of studies in current literature focused exclusively on assessing patients' willingness to pay (WTP) for pharmaceutical care services (Friedrich et al, 2010;Hill & Dowse, 2007;Hong et al, 2011;Schuh & Droege, 2008;Tootelian et al, 2005;Waszyk-Nowaczyk et al, 2014;Woelfel et al, 2014). Of those, Hong et al (2011) study did not intend to measure WTP in an overall MTM service, but to identify the marginal WTP for specific MTM attributes, such as service setting, provider's geriatric experience, and provider types etc.…”
Section: Willingness-to-pay For the Servicementioning
confidence: 99%